Lychee seed extract improves growth performance and hepatic health in largemouth bass (Micropterus salmoides) fed high-fat diets: Novel insights from network pharmacology and in vivo validation - Zhenye Lin; Qi Li; Wenjie Chu; Shuling Bai; Shan Xie; Xiaotong Chen; Hao Chen; Zhipeng Zheng; Jiandong Zhu; Yongxin Liu; Yingying Yu; Tengfei Zhu (Aquaculture, 2027)

Study on separation and dynamic characteristics of ilmenite and chlorite regulated by structural parameters of spiral chute - Shuling Gao; Bochao Li; Chunyu Liu; Qian Wang; Xiaohong Zhou; Guixia Fan; Daoguang Teng (Minerals Engineering, 2026)

Ethylene-triggered membrane lipid catabolism mediated by the PpERF110/113-PpPLD2 regulatory module exacerbates chilling injury in peach fruit - Lufan Wang; Huijuan Zhou; Qiaocai Zhang; Shiying Zhang; Zhengwen Ye; Xiongwei Li; Mengyuan Chen; Ziyi Yuan; Xiangzhen Sun; Lichao Zhou; Shuling Shen; Xiaolin Zheng; et al. (Postharvest Biology and Technology, 2026)

Designing sustained-release sodium carriers: Oil-modified starch gels enhance the texture and delay sodium release in low-sodium shrimp protein gels - Menghan Wang; Yang Li; Xuening Yu; Rui Liu; Shuling Zhou; Xiaoyang Liu; Dayong Zhou (Food Chemistry, 2026)

High-resolution urban air temperature mapping and interpretable multi-scale built-environment analysis for climate adaptation in a severe cold-region city - Qi Jia; Jingsi Xie; Fanyu Zeng; Dongliang Han; Shuling Li; Min Zhang; Tiantian Zhang; Lin Lu (Building and Environment, 2026)

Dynamic competitive constraint handling for constrained multi-objective optimization - Wei Li; Haoying Li; Ning Yang; Shuling Yang; Ying Huang (Swarm and Evolutionary Computation, 2026)

Multifunctional drug-loaded cement for microenvironment remodeling to promote osteoporotic bone regeneration in Kümmell's disease - Dongping Wang; Yihan Gao; Shuling Gu; Ziqi Feng; Zhizhao Li; Guanxiong Wang; Chang Liu; Yihao Zhu; Yang Shao; Qingtao Li; Yongxian Li; Xiaodong Cao; et al. (Chemical Engineering Journal, 2026)

White Spot Syndrome Virus Envelope Protein VP 53 B Functions as a Trypsin Inhibitor and Interacts With Hemocyanin - Wenxu Xia; Lingqi Zhuang; Yuchen Liu; Kai Li; Bing Qin; Shuling Yan; Yongxin Yu; Yongjie Wang (Journal of Fish Diseases, 2026)
White spot syndrome virus (WSSV) remains a persistent and significant threat to the global shrimp aquaculture industry. However, its pathogenic mechanisms remain incompletely understood, and no effective intervention strategies are currently available. In this study, we investigated the functional role of VP53B, an envelope structural protein of WSSV, using a combination of infection bioassays, protein structure prediction, protease inhibition assays and protein binding analyses. Our results demonstrate that VP53B is a critical determinant of per os (oral) infection in shrimp, including Procambarus clarkii (crayfish) and Litopenaeus vannamei (whiteleg shrimp). Functionally, VP53B acts as a trypsin inhibitor and interacts with host hemocyanin. We propose that through modulation of shrimp trypsin and hemocyanin, VP53B disrupts the prophenoloxidase‐activating system, a key innate immune pathway, thereby facilitating successful WSSV infection. This study provides new insights into the molecular mechanisms underlying WSSV oral infectivity and highlights VP53B as a potential target for therapeutic intervention.

Ameliorative effects of dietary curcuminoid supplementation on high-carbohydrate-diet-induced hepatic lipid metabolic disorders in largemouth bass (Micropterus salmoides) - Zhenye Lin; Zhipeng Zheng; Hongmian Mao; Wenjie Chu; Xiaotong Chen; Shan Xie; Shuling Bai; Qi Li; Hao Chen; Yongxin Liu; Jiandong Zhu; Tengfei Zhu; et al. (Aquaculture, 2026)

Europium-labeled polystyrene tracing reveals earthworm-mediated inhibition of root uptake and reduced phytotoxicity in lettuce - Nan Chang; Shiqi Bian; Qingliang Cui; Shuling Zhao; Tianyi Qiu; Li Chen; Tao Li; Peng-yang Wang; Roland Bol; Na Wang; Zhiqin Zhang; Fengyu Huang; et al. (Journal of Hazardous Materials, 2026)

Data-driven optimization of volatile fatty acid production from food waste in mono- and sludge-integrated co-fermentation systems - Fangnon Firmin Fangninou; Zhengguo Li; Zhan Yu; Guodong Yang; Dan Yu; Shuling Chen (Journal of Environmental Sciences, 2026)

Coupled impacts of climate change and urban morphology on building energy demand and outdoor thermal comfort in Harbin, China - Qi Jia; Jiayi Li; Tiantian Zhang; Lin Lu; Shuling Li (Building and Environment, 2026)

Astragaloside IV attenuates arsenic trioxide-induced cardiac toxicity in rats via the p38 MAPK/NF-κB signaling pathway - Weiyue Jin; Shuling Fei; Jing Li; Yurun Xue; Boli Wang; He Tang; Xue Han; Jie Cheng; Shengjiang Guan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Engineering hydrodynamics via pitch-diameter ratio to intensify eco-efficient separation of fine hematite/quartz in spiral chute - Shuling Gao; Qian Wang; Xiaohong Zhou; Chunyu Liu; Bochao Li (Minerals Engineering, 2026)

Hydrothermal depolymerization of PET microplastics assisted by pyroelectric-induced polarization in BTO/TiO₂ composite - Shuling Shen; Ziwei Feng; Huixin Feng; Zijian Zhang; Tongxin Huang; Zhihong Tang; Xinjuan Liu; Jing Li; Huixin Xiu (Journal of Environmental Chemical Engineering, 2026)

Unveiling the occurrence of legacy and novel per- and polyfluoroalkyl substance in a Hebei Tourist Region, China: A combined target screening and computational toxicology study - Shuling Luo; Jie Li; Ning Zhang; Yanwei Li; Xinlei Li; Zongchao Huo; Shilong Ren; Ting Wang; Wanqian Guo (Journal of Environmental Chemical Engineering, 2026)

Influences of environmental factors on the microbial community characteristics of bioaerosols in a cold region - Nami Lai; Shuozhen Tian; Silu Wang; Xiaoyan Wang; Ruihan Chen; Yuwei Liu; Huize Yang; Mengying Wang; Xiaoyu Cai; Wanying Yao; Shuling Li; Yue Xiao; et al. (Journal of Environmental Sciences, 2026)

Selection of adsorption and immobilization carriers under circulating flow conditions for enhanced performance and metabolic characteristics of Acidithiobacillus ferrooxidans - Fangzheng Zhou; Guanghui Chen; Yanyan Wang; Deshuang Yu; Yifan Zhu; Renjie Lu; Shufang Li; Shuling Xiao; Yingying Dong (Bioresource Technology, 2026)

Chronic Fluoride Exposure from Brick Tea Consumption Disrupts Bone Remodeling and Contributes to Bone Loss in Chinese Population with Skeletal Fluorosis - Hongjiang Long; Yubo Liu; Pinggui Lei; Ting Hu; Zhijuan Shao; Yu Luo; Shuling Zhang; Jinshu Li; Peng Luo; Zhenting Zhang; Shaofeng Wei (Biological Trace Element Research, 2026)

Endoscopic prediction model for detecting advanced rectal polyps after ileorectal anastomosis in familial adenomatous polyposis: a dual-center retrospective study - Zhilin Liu; Xingjie Gao; Shuling Chen; Linfu Zheng; Binbin Xu; Gaozhen Deng; Wen Wang; Kun Lin; Chushu Li; Zhou Ye; Dazhou Li (Familial Cancer, 2026)

Herbacetin alleviates acute doxorubicin cardiotoxicity via regulating the ERK1/2-FOXO3a signaling pathway - Sijia Bian; Xinran Li; Peiyan Zhu; Zhiting Jiang; Chen Yan; Shuling Wei; Liqi Luo; Yuhua Zhu; Lan Luo (Human Cell, 2026)

N-doped CoFe alloy coupled to hierarchical carbon as 3D catalysts for synergistic reversible oxygen electrocatalysis in Zn-air batteries - Ze Li; Tianfeng Ma; Zhen Feng; Haiyan Wang; Shuling Liu; Yanyan Liu; Hucheng Zhang; Jianji Wang; Baojun Li (Chemical Engineering Journal, 2026)

Quasi-solid-state electrolytes enabling long-life flexible electrochromic energy storage smart windows - Li Liao; Shuling Xiang; Biyou Bao; Guanglong Xu; Chengli Zhang; Qiang Wang; Zhenhu Cao; Wentao Chen; Hongtao Cao; Hongliang Zhang (Chemical Engineering Journal, 2026)

Multiplex PCR and nanopore sequencing reveal the genetic stability of Hantaan virus in Xi’an, China - Hailong Chen; Peng Zhang; Xiaoyue Chu; Yangni Deng; Mengying Yu; Leile Zhang; Quanli Du; Yuewen Han; Yujie Yang; Zerun Xue; Shuling Li; Rui Wu; et al. (Archives of Virology, 2026)

Enzyme immobilization on nanomaterials in food industry: current status and future perspectives - Lang Du; Yingzhuo Liang; Sifan Cui; Jianyang Wei; Jianqiao Liu; Shuling Zhang; Yuqing Zhang; Liya Zhou; Ying He; Li Ma; Jing Gao; Yanjun Jiang (Critical Reviews in Food Science and Nutrition, 2026)

Aquaculture conversion triggers iron-driven organic carbon destabilization in Estuarine Wetlands - Junpeng Li; Qingsong Zeng; Shuling Tang; Yingzi Wu; Yi Zheng; Weiqi Wang; Peipei Xue; Jordi Sardans; Josep Peñuelas (Plant and Soil, 2026)

Cross-kingdom synthetic microbial community alleviates Cd toxicity and inhibits its uptake in rice - Xiaozhen Zhu; Qi Sun; Peiyu Li; Qingxuan Lu; Shuling Zhao; Li Chen; Shaoyuan Zhang; Hansong Chen (Applied Soil Ecology, 2026)

Boosting methanogenesis in high-solids anaerobic digestion of corn straw by coupling hydrogen nanobubbles with biochar - Chuanfei Bian; Yiming Shi; Mao Du; Shuaishuai Ma; Shiyu Li; Hao Liu; Luyao Wei; Shuling Cao; Binshou Wang; Hongliang Wang; Wanbin Zhu (Journal of Environmental Chemical Engineering, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

Exogenous melatonin activates BoNAC52-BoRBOHF module and antioxidant system involved in the delay in broccoli yellowing during postharvest - Yue Wang; Lufan Wang; Yuting Li; Wenbo Lei; Jianhui Cheng; Yuan Cheng; Shuling Shen; Lanying Yao; Lichao Zhou; Yan Liu; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2025)

Optimization of fermentation conditions for propionic acid production by immobilized cells of Propionibacterium acidipropionici with sodium alginate-polyvinyl alcohol - Shuling Tang; Yingzi Wu; Junpeng Li; Yi Zheng (Biomass and Bioenergy, 2025)

1-MCP regulates taste development in cold-stored peach fruit through modulation of sugar, organic acid, and polyphenolic metabolism - Huijuan Zhou; Zhengwen Ye; Lufan Wang; Shiying Zhang; Ziyi Yuan; Mingshen Su; Xianan Zhang; Jihong Du; Xiongwei Li; Minghao Zhang; Yang Hu; Shuling Shen; et al. (Postharvest Biology and Technology, 2025)

Molecular interactions and physiological effects of oyster-derived synthetic peptide-calcium complex: Insight in improving the bone growth and health - Xuening Yu; Guang Li; Shijie Dou; Shuling Zhou; Xiaoyang Liu; Dayong Zhou (Food Research International, 2025)

Simultaneous electrodeposition of vanadium oxide and polyaniline derivatives and its application in aqueous zinc ion storage - Xiaojuan Lai; Yihao Li; Jiafei Niu; Jiatuo Li; Yuhang Cao; Shuling Liu; Chao Wang (Chemical Engineering Journal, 2025)

Impacts of shale gas wastewater leaks on neighboring crops: Physiological and morphological responses of tomatoes - Fengming Li; Xulin Yu; Yushun Yang; Wei Tao; Mengting Zhu; Di Zhang; Shuling Shi; Huiqiang Li; Peng Tang; Alberto Tiraferri; Baicang Liu (Process Safety and Environmental Protection, 2025)

Influence of ionic concentration in sludge on its deep dewatering behavior and electro-kinetic process - Xiaoyan Yu; Yingte Li; Sumeng Du; Saisai Su; Shuling Zhang (Journal of Water Process Engineering, 2025)

Overexpression of OsGASR1 promotes Al tolerance in rice - Shuling Cao; Liyun Peng; Jinyu Yu; Ziheng Li; Zhigang Wang; Dan Ma; Xiaoqian Sun; Huawei Zheng; Baolei Zhang; Xingxiang Chen; Zhufeng Chen; Jixing Xia (Plant Science, 2025)

Moisture-absorbing expansion and cracking characteristics of central Sichuan red-bed mudstone based on digital speckle correlation method - Kang Huang; Zhangjun Dai; Shuling Huang; Fei Yu; Shichang Li; Kaiwen Tong; Wei Zhang; Shanxiong Chen (Bulletin of Engineering Geology and the Environment, 2025)

Measurement and modelling of soil water dynamics under ridge tillage in paddy field - Lihua Ma; Shuling Wang; Chengsheng Ni; Wene Wang; Shaozhong Kang; Zhaolei Li; Alan L. Wright; Xianjun Jiang (Soil and Tillage Research, 2024)

Gas charging and accumulation in deep coal measures of Daning-Jixian Block, Ordos Basin: insights from fluid inclusions and basin modeling - Zhanwei Li; Song Li; Dazhen Tang; Shuling Tang; Jiaosheng Yang; Wei Hou (Frontiers of Earth Science, 2024)

Unveiling the impacts of microplastic pollution on soil health: A comprehensive review - Nan Chang; Li Chen; Na Wang; Qingliang Cui; Tianyi Qiu; Shuling Zhao; Haoran He; Yi Zeng; Wei Dai; Chengjiao Duan; Linchuan Fang (Science of The Total Environment, 2024)

Synergistic enhancement of plant growth and cadmium stress defense by Azospirillum brasilense and plant heme: Modulating the growth–defense relationship - Qingliang Cui; Jingzi Beiyuan; Yinglong Chen; Mengdi Li; Tianyi Qiu; Shuling Zhao; Xiaozhen Zhu; Hansong Chen; Linchuan Fang (Science of The Total Environment, 2024)

Effective and mechanistic insights into shale gas wastewater reverse osmosis concentrate treatment using ozonation-biological activated carbon process - Mengting Zhu; Peng Tang; Xulin Yu; Fengming Li; Shuling Shi; Di Zhang; Jialin Shi; Wei Tao; Xia Ruan; Lujian Liu; Baicang Liu (Science of The Total Environment, 2024)

Exogenous melatonin delays yellowing in postharvest broccoli by regulation of ABA and carotenoid metabolite - Ran Yan; Mariama Kebbeh; Yuan Cheng; Yue Wang; Yuting Li; Maorun Fu; Yan Liu; Chen Huan; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2024)

Multigenerational effects of disperse blue 79 at environmentally relevant concentrations on zebrafish (Danio rerio) fecundity: An integrated approach - Chao Wang; Wen Gu; Shaoping Zhang; Li Li; Jian Kong; Hong Zhi; Juan Liu; Mengmeng Wang; Ke Miao; Qi Li; Jie Yu; Runming Wang; et al. (Journal of Hazardous Materials, 2024)

Comparative transcriptomics analysis-guided metabolic engineering of Yarrowia lipolytica for improved erythritol and fructooligosaccharides production - Shuling Yang; Yanan Li; Baomin Guo; Jiajia You; Xian Zhang; Minglong Shao; Zhiming Rao (Bioresource Technology, 2024)

Gas content evaluation in deep coal seam with an improved method and its geological controls - Haiqi Li; Shida Chen; Dazhen Tang; Shuling Tang; Jiaosheng Yang (Frontiers of Earth Science, 2024)

High-throughput relative quantification of fatty acids by 12-plex isobaric labeling and microchip capillary electrophoresis - Mass spectrometry - Zicong Wang; Miyang Li; Shuling Xu; Liang Sun; Lingjun Li (Analytica Chimica Acta, 2024)

Insights into the catalytic mechanism of V-Mo@CN for the oxidation of 5-hydroxymethylfurfural to 2,5-diformylfuran - Shibo Yang; Tong Sun; Xiaokai Li; Wenbo Liao; Jianfei Bian; Xing Tang; Shuling Yang; Lu Lin; Wei Jiang; Lincai Peng; Yong Sun (Chemical Engineering Journal, 2024)

Self-sacrificed construction of versatile nanoadjuvant for synergistically enhanced immunogenic cell death and improved anti-tumor immunity - Peng Hu; Xiaowen Peng; Shuang Zhao; Fan Li; Guoye Yang; Wujie Guo; Shuling Yu; Jianjun Cheng; Juan Cen; Jiahua Shi (Chemical Engineering Journal, 2024)

Comparison of the osteogenic potential of fibroblasts from different sources - Jiaojiao Li; Liangliang Fu; Qian Lu; Shuling Guo; Si Chen; Ting Xia; Min Wang; Liangwen Chen; Yi Bai; Haibin Xia (Tissue and Cell, 2024)

Meta-analysis of impacts of microplastics on plant heavy metal(loid) accumulation - Li Chen; Nan Chang; Tianyi Qiu; Na Wang; Qingliang Cui; Shuling Zhao; Fengyu Huang; Hansong Chen; Yi Zeng; Faqin Dong; Linchuan Fang (Environmental Pollution, 2024)

Interaction of microplastics with heavy metals in soil: Mechanisms, influencing factors and biological effects - Baiyan Liu; Shuling Zhao; Tianyi Qiu; Qingliang Cui; Yuyi Yang; Lili Li; Jing Chen; Min Huang; Ai Zhan; Linchuan Fang (Science of The Total Environment, 2024)

Effect of heat input on the mechanical properties of welded Q960E ultra-high strength steel butt joints - Shuling Gao; Yanan Yue; Dan Zhang; Ning Li; Yiming Huang; Jiabao Yan; Lijun Yang (Engineering Structures, 2024)

An efficient three-dimensional (3D) inversion algorithm for recovering magnetic targets when remanence exists - Yuan Fang; Shuling Li; Guofeng Liu; Xiaohong Meng; Jun Wang; Shijing Zheng (Acta Geophysica, 2024)

HNF4A as a potential target of PFOA and PFOS leading to hepatic steatosis: Integrated molecular docking, molecular dynamic and transcriptomic analyses - Rui Li; Zijing Zhang; Yuxin Xuan; Yulu Wang; Yuyan Zhong; Lingyin Zhang; Jinrui Zhang; Qian Chen; Shuling Yu; Jintao Yuan (Chemico-Biological Interactions, 2024)

Systematic metabolic engineering of Yarrowia lipolytica for the enhanced production of erythritol - Shuling Yang; Xuewei Pan; Jiajia You; Baomin Guo; Zuyi Liu; Ying Cao; Guomin Li; Minglong Shao; Xian Zhang; Zhiming Rao (Bioresource Technology, 2024)

Real-time hybrid simulation incorporating machine learning for deep-water bridges subjected to seismic ground motion with fluid-structure dynamic interaction - Zihao Zhou; Dan Zhang; Yafei Zhang; Ning Li; Shuling Gao; Yanan Yue (Soil Dynamics and Earthquake Engineering, 2023)

Role of antenatal anxiety in the relationship between maternal exposure to nitrogen dioxide and small for gestational age: A birth cohort study - Qiannan Wei; Weiwei Lin; Hedi Zhang; Yuming Lai; Shuling Zhuang; Zhenyan Han; Qingqing Wang; Lijie Wang; Wenzhuo Li; Li Wen; Hongying Hou; Qiansheng Hu (Science of The Total Environment, 2023)

Insights into boosting catalytic hydrogen evolution over Co doping Ru nanoparticles - Hao Wen; Ruofan Shen; Yanyan Liu; Xiaoyan Huang; Shuling Liu; Zhikun Peng; Xianli Wu; Xianji Guo; Erjun Liang; Huiyu Yuan; Baojun Li; Jianchun Jiang (Fuel, 2023)

In-depth insight into correlations between gut microbiota and dietary fiber elucidates a dietary causal relationship with host health - Lili Li; Shuling Yan; Shuangjiang Liu; Ping Wang; Wenjun Li; Yuetao Yi; Song Qin (Food Research International, 2023)

Establishment of a prognostic model for melanoma based on necroptosis-related genes - Xiaohui Sui; Xiaodan Zhang; Junde Zhao; Jinxing Liu; Shuling Li; Xiaowen Zhang; Juntao Wang (Functional & Integrative Genomics, 2023)

Bacterial diversity of middle ear cholesteatoma by 16S rRNA gene sequencing in China - Qiulin Liang; Ruiqing Long; Shuling Li; Chaowu Jiang; Jingyu Gao; Sheng Cheng; Zhuohui Liu; Biao Ruan (Functional & Integrative Genomics, 2023)
In this study, the bacterial diversity of acquired middle ear cholesteatoma (MEC) was evaluated to reveal its pathogenesis and provides a guide for the use of antibiotics. Twenty-nine cases of acquired MEC and eight cases of healthy middle ears undergoing cochlear implantation (CI) were evaluated. Full-length 16S rRNA gene sequencing was performed to profile the bacterial communities in lesions and healthy tissues of the middle ear. ACE ( P = 0.043) and Chao1 ( P = 0.039) indices showed significant differences in alpha diversity ( P < 0.05). Analysis of PERMANOVA/Anosim using the Bray–Curtis distance matrix results suggested that the between-group differences were greater than the within-group differences ( R = 0.238, P < 0.05, R 2 = 0.066, P < 0.05). Bacterial community analysis revealed that Alphaproteobacteria at the class level and Caulobacterales and Sphingomonadales at the order level were significantly different ( P < 0.05). In the LefSe (Linear discriminant analysis effect size) analysis, Porphyromonas bennonis was elevated, and Bryum argenteum and unclassified Cyanobacteriales were reduced at the species level in MEC ( P < 0.05). Fifteen metabolic pathways were found to be significantly different between the two groups by analysing the abundance of metabolic pathways in level 2 of the Kyoto Encyclopaedia of Genes and Genomes (KEGG). Seven and eight metabolic pathways were significantly elevated in the MEC and control groups, respectively ( P < 0.05). The role of bacteria in the pathogenesis of acquired MEC was further refined through analysis of metabolic pathways. These findings indicate that the acquired MEC and healthy middle ear contain more diverse microbial communities than previously thought.

An improved method for estimating soil moisture over cropland using SAR and optical data - Dayou Luo; Xingping Wen; Shuling Li (Earth Science Informatics, 2023)

Capture of copper cyanide complex ions based on self-assembly of ionic liquids actuation and application to cyanide wastewater - Weichao Li; Wengang Liu; Wenbao Liu; Shijie Zhou; Shuling Gao; Yanbai Shen (Hydrometallurgy, 2023)

Temperature effects on microbial dissolved organic matter metabolisms: Linking size fractions, fluorescent compositions, and functional groups - Gang Tang; Binrui Li; Bowei Zhang; Shiwen Hu; Shuling Chen; Tong Liu; Qianqian Wang; Han Qiao; Xing Zheng (Science of The Total Environment, 2023)

Prediction of the Endocrine disruption profile of fluorinated biphenyls and analogues: An in silico study - Yuyan Zhong; Jing Ren; Rui Li; Yuxin Xuan; Wu Yao; Qianye Yang; Yin Gan; Shuling Yu; Jintao Yuan (Chemosphere, 2023)

Experimental and numerical study on seismic performance of precast segmental CFST bridge columns with non-uniform prestressed steel tendons - Dan Zhang; Zihao Zhou; Shuling Gao; Yanan Yue; Yafei Zhang; Ning Li (Engineering Structures, 2023)

Transcriptome analysis reveals the mechanisms of hepatic injury caused by long-term environmental exposure to atrazine in juvenile common carp (Cyprinus carpio L.) - Jingbo Liu; Guangcheng Yang; Yanxia Gao; Xinran Li; Yuting Long; Shuling Wei; Yuxin Zhao; Shanshan Sun; Shujuan Gao (Environmental Science and Pollution Research, 2022)

Effect of confining pressure on peak penetration force of the TBM disc cutter - Wu Li; Peng Yan; Ang Lu; Shuling Huang; Wenbo Lu (Arabian Journal of Geosciences, 2022)

Heat shock cognate protein 70 is required for rice stripe tenuivirus accumulation and transmission in small brown planthopper - Jie Li; Wenyu Pan; Shuling Zhao; Changyong Liang (Archives of Virology, 2022)

Effect of urea feeding on transforming and migrating soil fluorine in a tea garden of hilly region - Hua Long; Yamei Jiang; Chaoqun Li; Shuling Liao; Shuyu Shi; Chunping Huang; Shilin Zhao; Xiaoting Li; Yang Liao (Environmental Geochemistry and Health, 2021)

Characterization of Water Quality in Xiao Xingkai Lake: Implications for Trophic Status and Management - Shuling Yu; Xiaoyu Li; Bolong Wen; Guoshuang Chen; Anne Hartleyc; Ming Jiang; Xiujun Li (Chinese Geographical Science, 2021)

Petrogenesis and tectonic setting of Late Devonian I-type granitic plutons in the Kekesala area, Chinese western Tianshan: implication for tectonic evolution of the North Tianshan Ocean - Zuopeng Wang; Yongjun Li; Gaoxue Yang; Le Wu; Yu Wan; Philemon Lindagato; Shuling Li (International Geology Review, 2021)

The N-terminal cysteine protease domain of rice stripe tenuivirus Pc1 possesses deubiquitinating enzyme activity - Shuling Zhao; Xiaomei Gu; Jie Li; Changyong Liang (Virus Genes, 2021)

Pyr-miR171f-targeted PyrSCL6 and PyrSCL22 genes regulate shoot growth by responding to IAA signaling in pear - Shuling Jiang; Qiuju Chen; Qiulei Zhang; Yi Zhang; Ningning Hao; Chunqing Ou; Fei Wang; Tianzhong Li (Tree Genetics & Genomes, 2018)

Construction of an Off-On Fluorescence System Based on Carbon Dots for Trace Pyrophosphate Sensing - Qiaoli Yue; Yining Hou; Shuzhen Yue; Kaimin Du; Tongfei Shen; Lei Wang; Shuling Xu; Haibo Li; Jifeng Liu (Journal of Fluorescence, 2015)

Quantitative structure–activity relationship studies of diarylpyrimidine derivatives as anti-HIV drugs using new three-dimensional structure descriptors - Jianbo Tong; Li Zhong; Xiang Zhao; Shuling Liu; Ping Wang (Medicinal Chemistry Research, 2014)

CXCL12 induces lung cancer cell migration by polarized mtDNA redistribution - Jietao Ma; Jiahe Zheng; Yaoyong Li; Shuling Zhang; Dongmei Bai; Huawei Zou; Chengbo Han (Human Cell, 2014)

Successful application of optimized aperture based CRS stack in the Shengli exploration area - Fenggui Sui; Shuling Sui; Zhenchun Li; Xiaodong Sun; Fang Li; Dong Li (Applied Geophysics, 2009)

A method for gravity anomaly separation based on preferential continuation and its application - Xiaohong Meng; Lianghui Guo; Zhaoxi Chen; Shuling Li; Lei Shi (Applied Geophysics, 2009)

Patterns of variation of the major histocompatibility complex class IIB loci in Chinese goose (Anser Cygnoides) - Xu Zhou; Chunjin Li; Kangle Yi; Hongyan Liang; Lu Chen; Yanling Sun; Shuling Niu; Wei Wu (Immunogenetics, 2009)

Oct4 is expressed in Nestin-positive cells as a marker for pancreatic endocrine progenitor - Hong Wang; Shuling Wang; Jiang Hu; Yaxian Kong; Shen Chen; Lingsong Li; Liying Li (Histochemistry and Cell Biology, 2009)

Human embryonic germ cells isolation from early stages of post-implantation embryos - ShanRong Liu; HouQi Liu; YuQiong Pan; ShuPing Tang; Jun Xiong; Ning Hui; ShuLing Wang; ZhongTian Qi; LingSong Li (Cell and Tissue Research, 2004)